Elucidating the Correlation of D-Dimer Levels with COVID-19 Severity: A Scoping Review. (8th March 2022) - Nasif, Wesam Ahmed; El-Moursy Ali, Abeer Shaker; Hasan Mukhtar, Mohammed; Alhuzali, Aali Marzouq H.; Yahya Alnashri, Yahya Ahmed; Ahmed Gadah, Ziyad Ishaq; Edrees, Eyyad Adeeb A.; Albarakati, Hussam Abdulaziz Mabruk; Muhji Aloufi, Hussam Saud
Abstract : Aims . The review explores the findings of previous studies to elucidate the association between levels of D-dimer and COVID-19 severity and prognosis. In addition, we assessed the efficiency of anticoagulant therapies in reducing COVID-19 severity and improving the prognosis of the patients. Materials and Methods . A comprehensive literature review was conducted using MEDLINE/PubMed databases, Scopus, and Web of Science with the help of keywords "COVID-19, " "D-Dimer, " "Thrombosis, " "Fibrin network, " "Anticoagulant therapy, " "Inflammation, " and "disease severity." Based on all these articles and clinical experience, a scoping review was constructed and the full texts of the articles that were retrieved were accessed. Results . A D-dimer is a complex protein molecule that is formed during plasmin-mediated degradation of the fibrin network. Thus, it serves as a marker of thrombotic activity. On the other hand, in addition to severe respiratory distress and reduction in pulmonary gas exchange, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) also triggers prothrombotic changes in the infected individuals. The levels of D-dimer have been postulated to be positively associated with the degree of disease severity among COVID-19 patients. Conclusions . It has been postulated that D-dimer could potentially be used as a biomarker to predict the prognosis and outcome of COVID-19 patients at the time of admission to hospitals and facilitate more personalized and efficient clinical management that could significantly reduce the mortality rate of such patients and allow more rapid recovery.